The effects of establishing a hydrogen industry in Northern Germany - Andreas Lagemann; Stephen Sacht (Hamburg Institute of International Economics (HWWI), 2025)
Currently, achieving sustainable transformation toward a carbon-dioxide-free industrial production process is one of the greatest challenges. The chemical element hydrogen used as an energy source and a basic feedstock can play an important role in reaching this goal. Our analysis is based on the CGE framework and focuses on a total switch toward hydrogen used in production in northern Germany until 2045. The simulation results indicate that such a cost-intensive procedure can lead not only to a negative development in regional GDP and employment but also to a decline in the output of heavy industries such as chemical, steel, and copper. Reverse effects are obtained in the case of further deregulation, which has the potential to increase the efficiency of an established hydrogen core network. This observation emphasizes the need to accompany the transformation process by maintaining low-level regulation. – – Die nachhaltige Transformation hin zu einem kohlendioxidfreien industriellen Produktionsprozess stelle eine große Herausforderung dar. Das chemische Element Wasserstoff kann als Energieträger und Rohstoff einen wichtigen Beitrag zur Erreichung dieses Ziels leisten. Unsere Analyse basiert auf einem CGE-Modell und konzentriert sich auf eine vollständige Umstellung der Produktion auf Wasserstoff in Norddeutschland bis 2045. Die Simulationsergebnisse zeigen, dass ein solch kostenintensiver Prozess nicht nur zu einer negativen Entwicklung des regionalen BIP und der Beschäftigung, sondern auch zu einem Rückgang der Produktion in der Schwerindustrie wie der Chemie-, Stahl- und Kupferindustrie führen kann. Umgekehrte Effekte ergeben sich bei einer weiteren Deregulierung, die das Potenzial hat, die Effizienz eines bestehenden Wasserstoff-Kernnetzes zu steigern. Diese Beobachtung unterstreicht die Notwendigkeit, den Transformationsprozess durch die Beibehaltung einer dezenten Regulierung zu begleiten.
Keywords: C68; O13; Q21; R13; 330; Computable General Equilibrium Model Analysis; Hydrogen Economy; Regional and Industrial Development; Northern Germany; Regulations